Observations beneath Pine Island Glacier in West Antarctica and implications for its retreat - Jenkins, Adrian; Dutrieux, Pierre; Jacobs, Stanley S.; McPhail, Stephen D.; Perrett, James R.; Webb, Andrew T.; White, David (Nature Geoscience, 2010)
Thinning ice in West Antarctica, resulting from acceleration in the flow of outlet glaciers, is at present contributing about 10% of the observed rise in global sea level. Pine Island Glacier in particular has shown nearly continuous acceleration and thinning, throughout the short observational record. The floating ice shelf that forms where the glacier reaches the coast has been thinning rapidly, driven by changes in ocean heat transport beneath it. As a result, the line that separates grounded and floating ice has retreated inland. These events have been postulated as the cause for the inland thinning and acceleration. Here we report evidence gathered by an autonomous underwater vehicle operating beneath the ice shelf that Pine Island Glacier was recently grounded on a transverse ridge in the sea floor. Warm sea water now flows through a widening gap above the submarine ridge, rapidly melting the thick ice of the newly formed upstream half of the ice shelf. The present evolution of Pine Island Glacier is thus part of a longer-term trend that has moved the downstream limit of grounded ice inland by 30 km, into water that is 300 m deeper than over the ridge crest. The pace and ultimate extent of such potentially unstable retreat are central to the debate over the possibility of widespread ice-sheet collapse triggered by climate change.